Dewan Perwakilan Daerah Menurut UUD 1945 Dan Penerapan Sistem Bikameral Dalam Lembaga Perwakilan Indonesia - Bardjo Bardjo (Fakultas Hukum Universitas Islam Indonesia, 2007)
Formally, Indonesia adopts bicameral system as there are the House of Representatives (DPR) and the Regional Representatives Council (DPD). However, structurally, it could be deemed ad tricameral, as there are three representative bodies available; People’s Consultative Assembly (MPR), House of Representatives (DPR) and the Regional Representatives Council (DPD). Thus, practically, Indonesian parliamentary system is unicameral since the authority for legislation lies in the hand of the members of the House of Representatives (DPR).